Determination of bioavailable dissolved Fe(III) at different fractionation sizes at coastal water by adsorptive-cathodic stripping voltammetry - Ramjam, Nur Jannati; Mohamed, Khairul Nizam (Elsevier, 2022)
The concentration of Fe(III) was determined at different dissolved fractionation, which is small colloidal Fe(III) (< 0.20 μm) and dissolved Fe(III) (< 0.45 μm) to identify the phase partitioning of bioavailable Fe(III) at Pulau Redang, Terengganu. The determination was obtained by using a newly developed adsorptive-cathodic stripping voltammetry (AdCSV) method with 2,3-dihydroxynapthalene (DHN) as a binding ligand. The results show an increase in the concentration of dissolved Fe(III) compared to small colloidal Fe(III); however, no significant differences are found between both phases after being tested by statistical analysis. The increased concentration of Fe(III) in the dissolved phase was smaller (mean concentration = 16.64 pM) than previously reported (range concentration = 0.04 - 1.98 nM), suggesting that Fe(III) mainly existed as particulate Fe rather than as dissolved Fe during the period in our study area. Interestingly, the low concentration of Fe(III) was sufficient to support the growth of phytoplankton in our study area.